Conductivity, structure, and thermal properties of chitosan-based polymer electrolytes with nanofillers - Aziz, N.A.; Majid, Siti Rohana; Yahya, R.; Arof, Abdul Kariem (John Wiley & Sons, 2011)
This paper focus on the effect of nanosize (<50 nm BET) inorganic alumina (Al2O3) filler on the structural, conductivity, and thermal properties of chitosan-based polymer electrolytes. Films of chitosan and its complexes were prepared using solution-casting technique. Different amounts of Al2O3 viz., 3, 4.5, 6, 7.5, 9, 12, and 15 wt% were added to the highest room temperature conducting sample in the chitosan-salt system, i.e. sample containing 60 wt% chitosan-40 wt% NH4SCN. The conductivity value of the sample is 1.29x10(-4) S cm(-1). On addition of 6 wt% Al2O3 filler the ionic conductivity increased to 5.86x10(-4) S cm(-1). The amide and amino peaks in the spectrum of chitosan at 1636 and 1551 cm(-1), respectively, shift to lower wavenumbers on addition of salt. The glass transition temperature T-g for the highest conducting composite is 190 degrees C. The increase in T-g with increase in more than 6 wt% filler content is attributed to the increase in degree of crystallinity as proven from X-ray diffraction studies. Copyright (C) 2009 John Wiley & Sons, Ltd.